Disfunción familiar y su influencia en la salud mental de una mujer de 20 años del cantón Echeandía - Moposita Poma, Mirian Margoth (2023)
This case study was conducted with the objective of describing whether family dysfunction influences the mental health of a 20-year-old woman from the Echeandía canton, which is investigated through clinical history, semi-structured interview, clinical psychological observation, application of psychological tests such as the Family Functioning Questionnaire (FF-SIL), which identified the existence of family dysfunction, the Beck Depression Inventory detected depressive symptoms related to moderate depression that correlates with the DSM V diagnostic criteria, In the results obtained, it was possible to identify that throughout her life there were different risk factors such as alcohol and drug consumption, domestic violence, lack of limits and respect between parents and children, sexually transmitted diseases, disability, economic problems that influenced her dysfunctional family and led to damage to her mental health, However, through the psychological techniques of deep breathing and the ABC technique, it was possible to change the lifestyle, eliminate the feeling of social rejection and acceptance of physical (HIV) and psychological (depression) illnesses, reduce irrational thoughts, motivate a life project and eliminate physical symptoms.